Noninvertible symmetries from holography and branes - Apruzzi, F; Bah, I; Bonetti, F; Schafer-Nameki, S (American Physical Society, 2023)
We propose a systematic approach to deriving symmetry generators of quantum field theories in holography. Central to this analysis are the Gauss law constraints in the Hamiltonian quantization of symmetry topological field theories (SymTFTs), which are obtained from supergravity. In turn, we realize the symmetry generators from world-volume theories of D-branes in holography. Our main focus is on noninvertible symmetries, which have emerged in the past year as a new type of symmetry in d ≥ 4 QFTs. We exemplify our proposal in the holographic confinement setup, dual to 4D N = 1 Super-Yang Mills. In the brane picture, the fusion of noninvertible symmetries naturally arises from the Myers effect on D-branes. In turn, their action on line defects is modeled by the Hanany-Witten effect.